Evolution of the global use of unsafe medical injections, 2000-2010. - Jacques Pépin; Claire Nour Abou Chakra; Eric Pépin; Vincent Nault (PLoS ONE, 2013)
OBJECTIVE: Since 1999, substantial efforts have been made by the international community to reduce the risks associated with unsafe injections, through ministries of health, international donors, the World Health Organization and the Safe Injection Global Network. The present study attempted to measure the progress, or lack thereof, made over the 2000-2010 decade in reducing unsafe injections in ten regions of the world corresponding to developing and transitional economies. METHODS: Data about the number of injections per person per year and the proportion of re-use of syringes and needles were obtained for 2010, mainly from population surveys, and compared with previous estimates for 2000 which had used various sources of information including injection safety assessments, population surveys and published studies on injection practices. RESULTS: From 2000 to 2010, in developing countries and transitional economies, the average number of injections per person per year decreased from 3.40 to 2.88, while the proportion of re-use of injection devices dropped from 39.8% to 5.5%. Combining both factors the number of unsafe injections per person per year decreased from 1.35 to 0.16. Even if substantial progress has been made, the Eastern Mediterranean region remains problematic, with 0.57 unsafe injections per person per year. In sub-Saharan Africa and Latin America, people now receive on average only 0.04-0.05 unsafe injections per year. CONCLUSION: Substantial progress has been made in reducing the number of unsafe injections in developing countries and transitional economies, essentially through a reduction in the re-use of injection devices. In some regions, elimination of unsafe injections might become a reasonable goal.